FOREGROUNDING OF THE THEME OF CHANGE AND RENEWAL IN SHELLEY’S “ODE TO THE WEST WIND”: A STYLISTICS ANALYSIS (Contemporary Journal of Social Science Review, 2025)
This study explores the stylistic devices utilized by Percy Bysshe Shelley in his poem "Ode to the West Wind" and studies how these techniques contribute to the articulation of the poem’s central theme of change and renewal. This study uses a qualitative research design. This analysis focusses Shelley’s deliberate use of unusual diction, inventive grammar, and creative phraseology to evoke the dynamic energy of the poem. The study draws on leech and short (2007) to show that Shelley’s rare word choices, neologisms, syntactic creativity, and foregrounding are not merely decorative but serve to intensify the poem’s emotional impact and thematic resonance. The finding revealed that techniques such as asyndeton, creative deviation, and parallelism are shown to mirror the poem’s focus on transformation, while the poem’s visual structure and rapid enumerations reinforce its restless, energetic tone. The findings suggest that Shelley’s stylistic strategies enable the poem to portray the very change it describes, underscoring the interplay between language and the forces of nature. This analysis contributes to understanding of how Shelley’s poetic craft foregrounds the themes of transformation and renewal, positioning "Ode to the West Wind" as a vivid example of Romantic innovation in language and form.